Oleksandr Oleksijovych Kostrub - “Orthopaedics, Traumatology and Prosthetics”, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is dedicated to the head of the Department of Sports and Ballet Trauma of the State Institution "Institute of Traumatology and Orthopedics of the National Academy of Medical Sciences of Ukraine", doctor of medical sciences, professor, doctor of the highest qualification category O. O. Kostrub.